JURIDIC REVIEW ON THE MAINTENANCE OF LABOR HEALTH THROUGH THE BPJS PROGRAM - Pratama, Dito; Shaharani, Zahira; Ibrahimi, Abdallah (Khairun Law Journal, 2022)
Health Care Insurance is a form of health protection guarantee, with the intention that participants get health benefits or protection to meet health needs for everyone who has paid their dues or whose contributions have been borne by the government. National Social Security is a government and community plan designed to determine the amount of social welfare protection for all people in order to meet their needs and social welfare. The Social Security Administering Body (BPJS) is the institution that manages or operates the National Social Security System Plan (SJSN). But the form of implementation in BPJS is that many health insurance services are provided to participants whose needs are limited. This health service is needed by the community to overcome their health problems. With this research aims to be able to determine the health care insurance for workers associated with optimal health services for workers. In addition, it is also known the form of services provided by BPJS in protecting some rights to the health of workers.